Semantic Under-determinacy and Communication - Belleri, D. author. aut Link
X, 193 p.
Keywords: Combining a fresh, previously unexplored view of the subject with a detailed overview of the past and ongoing philosophical discussion on the matter, this book investigates the phenomenon of semantic under-determinacy by seeking an answer to the questions of how it can be explained, and how communication is possible despite it.